DYNAMICS OF CONJUGATION PATTERN "KUPUJE" IN CONTEMPORARY CZECH (ON MATERIAL OF JOURNALISTIC TEXTS, 1990-2019) - Bláha, Ondřej (Bohemica Olomucensia, 2022)
The conjugation pattern "kupuje" is a highly productive verb type in Czech: there are more than eight thousand records of verb neologisms belonging morphologically to the type "kupuje" in the database Neomat listed during the years 1990-2019. The peak of productivity of the "kupuje" type fell in the second half of the 1990s (the second, smaller peak of productivity came in 2011-2015). On the other hand, the frequency of verbs of the type "kupuje" in journalistic texts written in the last thirty years appears, as the corpus shows, to be steady and without significant fluctuations, both at the level of lemmas and at the level of tokens related to these lemmas. The frequency of imperfective verbs of the type "kupuje" is slightly increasing, while (in line with the general trend in Czech) the frequency of the bi-aspectual verbs of the type "kupuje" is decreasing. There is a noticeable increase in the frequency of imperfective verbs of the "kupuje" type with roots borrowed from foreign languages, while the representation of prefixed verbs among verbs of the "kupuje" type decreases. Regarding the formal variation of "kupuje" type (made possible by the latest codification of the Czech language in 1993), there is a significant increase in the frequency of forms of the 1st person sg. of present tense (progressive type kupuju "I am buying" vs. older kupuji) in written journalistic texts, the proportion of which has tripled over the last three decades. On the other hand, the 3rd person singular of present (progressive type kupujou "they are buying" vs. older kupují) are almost non-existent in written journalistic texts.
Keywords: Czech; morphology; verbal aspect; language change; neologisms; productivity; conjugation pattern "kupuje"